ChemInform Abstract: Diastereoselective Total Synthesis of Salvileucalin C. Issue 51 (23rd December 2014) - Fu, Chenchen; Zhang, Yuanbao; Xuan, Jun; Zhu, Chenlong; Wang, Bingnan; Ding, Hanfeng
Abstract The preparation of salvileucalin C (I) and its biosynthetically related diterpenoids salvileucalin D (II), salvipuberulin (III), isosalvipuberulin (IV) and dugesin B (V) is achieved.